(untitled) (Zaporizhzhia Historical Review, 2021)
Process of restoration of the activity of the organizations of the Russian socialists-revolutionaries turned at the end of 1905 in the Western Europe and South America considered insufficiently is studied. Emigrants who lived in Japan actively worked in 1905-1907 years under management Sudzilovskiy. The special attention is given to the analysis of their agitation-and-propaganda work.